Percepção ambiental de crianças e idosos habitantes de uma região estuarina no semiárido brasileiro - Regis, Laís Belmino (2025)
Mangroves are biodiverse ecosystems that provide multiple ecosystem services, including thermal regulation, coastal protection, and food production. Despite being protected by legislation, mangroves face anthropogenic threats such as deforestation and pollution. Understanding how different generations relate to the environment is essential for strengthening context-specific strategies for conservation and environmental education, directly contributing to the protection of sensitive ecosystems like mangroves. This research was conducted with the aim of analyzing the environmental perception of children and elderly residents of an estuarine region in the Brazilian semi-arid zone. The study site was the Pacoti River Environmental Protection Area (APA), located on the eastern coast of the state of Ceará, between the municipalities of Fortaleza, Eusébio, and Aquiraz, in a transitional zone between urban areas and coastal ecosystems. The research subjects were elderly people and children living in the Mangabeira neighborhood, Eusébio. This is a qualitative study, which, through an action research approach and in conjunction with environmental education activities carried out by the Marine Environmental Education Program (PEAM/UFC), sought to analyze participants' environmental perception and raise their awareness. Semi-structured interviews were conducted with 27 participants (15 children and 12 elderly individuals) in two phases: before and after the implementation of environmental education activities, such as guided ecological trails, art workshops, and discussion circles. The responses were transcribed and analyzed using IRaMuTeQ software, employing lexical analysis tools such as word clouds, similarity analysis, correspondence factor analysis, and the Reinert method. The results reveal significant changes in the socio-environmental representations of the participants after the educational activities, indicating a greater understanding of the environmental complexity of the APA, increased appreciation of the estuary, and recognition of the interactions between natural and social elements within the territory. The importance of rescuing traditional memories and knowledge was also observed in strengthening territorial identity and encouraging community participation. This research contributes to the field of critical environmental education by demonstrating how dialogical pedagogical practices, connected to local reality issues, can promote the formation of conscious, sensitive, and active individuals engaged in the environmental conservation of their territories.